Nursing research - Despotović Mile; Despotović Milena; Kekuš Divna; Stanojević Čedomirka; Marinović Nela; Ilić Biljana (Association of Nurses Technicians and Midwives, 2020)
With the development of nursing education institutions, there emerged a need for continued education and expansion of the body of related scientific knowledge. After the introduction of nursing care and nursing into the university curricula, scientific research in this area became an inevitable part of the advancement of the profession. Nursing focuses on the care for others and deals with issues such as nutrition, security and safety, admission and care, hygiene issues and similar. Promoting the research and involvement of nurses in research teams is of great importance to the quality of nurses' work, as it encourages evidence-based and data-based work. Generally speaking, we can say that the history of nursing research begins together with modern nursing. Nurses involved in research are often faced with a lack of support from managerial nurses and misunderstanding from colleagues who believe that doing research has a negative impact on clinical practice. Such a situation suggests that research work should actually be encouraged during school. There are three major areas with regard to nursing research: nursing education, nursing practice, and nursing administration. When it comes to trends in nursing education, the emphasis is primarily put on the importance of quality research rooted in philosophy and humanism that is also able to provide practically usable results. In the field of nursing practice, the emphasis is on research that promotes health and healthy lifestyles. Finally, in the field of nursing administration, the most common is evidence-based research. The primary focus is placed on topics such as nursing, energy therapies, knowledge and attitudes, and spirituality. The relationship between care and treatment, symptoms management, quality of life and depression are the topics most commonly examined. In Serbia, nurses have only recently been given the opportunity to study at a university level. There is also an increasing number of nursing colleges. This situation speaks in favor of stimulating and fostering research work.